2002
DOI: 10.1016/s1074-7613(01)00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Antigen-Presenting Function of MHC Class I Molecules in Cells Lacking the ER Chaperone Calreticulin

Abstract: MHC class I molecules expressed in a calreticulin-deficient cell line (K42) assembled with beta 2-microglobulin (beta2-m) normally, but their subsequent loading with optimal peptides was defective. Suboptimally loaded class I molecules were released into the secretory pathway. This occurred despite the ability of newly synthesized class I to interact with the transporter associated with antigen processing (TAP) loading complex. The efficiency of peptide loading was reduced by 50%-80%, and impaired T cell recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(203 citation statements)
references
References 44 publications
(1 reference statement)
12
190
1
Order By: Relevance
“…Ten years ago the hypothesis was that the abundant ERp57 found in the PLC was a consequence of its interaction with calreticulin or possibly calnexin (Oliver, Roderick et al 1999). However, coimmunoprecipitation from K42 cells (a calreticulin deficient embryonic mouse fibroblast cell line) showed complexes of calnexin together with ERp57, tapasin and HC suggesting an alternative PLC constellation lacking calreticulin (Gao, Adhikari et al 2002). Coimmunoprecipitation in lysates of K42 cells showed that ERp57 was associated with TAP, but that no calnexin could be detected in these precipitates, suggesting that neither calnexin nor calreticulin are essential for recruitment of ERp57 to the PLC (Suh, Mitchell et al 1996;Gao, Adhikari et al 2002).…”
Section: Lack Of Calreticulin But Not Calnexin Diminishes Mhc-i Quamentioning
confidence: 99%
See 3 more Smart Citations
“…Ten years ago the hypothesis was that the abundant ERp57 found in the PLC was a consequence of its interaction with calreticulin or possibly calnexin (Oliver, Roderick et al 1999). However, coimmunoprecipitation from K42 cells (a calreticulin deficient embryonic mouse fibroblast cell line) showed complexes of calnexin together with ERp57, tapasin and HC suggesting an alternative PLC constellation lacking calreticulin (Gao, Adhikari et al 2002). Coimmunoprecipitation in lysates of K42 cells showed that ERp57 was associated with TAP, but that no calnexin could be detected in these precipitates, suggesting that neither calnexin nor calreticulin are essential for recruitment of ERp57 to the PLC (Suh, Mitchell et al 1996;Gao, Adhikari et al 2002).…”
Section: Lack Of Calreticulin But Not Calnexin Diminishes Mhc-i Quamentioning
confidence: 99%
“…However, coimmunoprecipitation from K42 cells (a calreticulin deficient embryonic mouse fibroblast cell line) showed complexes of calnexin together with ERp57, tapasin and HC suggesting an alternative PLC constellation lacking calreticulin (Gao, Adhikari et al 2002). Coimmunoprecipitation in lysates of K42 cells showed that ERp57 was associated with TAP, but that no calnexin could be detected in these precipitates, suggesting that neither calnexin nor calreticulin are essential for recruitment of ERp57 to the PLC (Suh, Mitchell et al 1996;Gao, Adhikari et al 2002). More recently it has been shown that ERp57 is directly disulfide conjugated to tapasin in the PLC (Peaper, Wearsch et al 2005).…”
Section: Lack Of Calreticulin But Not Calnexin Diminishes Mhc-i Quamentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10] The first five of these associate to form the peptide-loading complex (PLC), which is believed to promote the assembly of peptide-receptive complexes with peptide within the ER. Unlike calreticulin, calnexin and ERp57, which have general chaperone functions, tapasin has a specialised role in MHC class I assembly.…”
Section: Introductionmentioning
confidence: 99%